2015
DOI: 10.4253/wjge.v7.i3.162
|View full text |Cite
|
Sign up to set email alerts
|

Intentional ingestions of foreign objects among prisoners: A review

Abstract: The intentional ingestion of foreign objects (IIFO) is described more commonly in prison populations than in the general population, with an estimated annual incidence of 1 in 1900 inmates in our state correctional facilities. Incidents often involve ingestion of small metal objects (e.g., paperclips, razor blades) or other commonly available items like pens or eating utensils. Despite ingestion of relatively sharp objects, most episodes can be clinically managed with either observation or endoscopy. Surgery s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…Secondary gain or undiagnosed psychiatric disease can explain the ingestion among prisoner population (6). Sugery is a very rare option.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary gain or undiagnosed psychiatric disease can explain the ingestion among prisoner population (6). Sugery is a very rare option.…”
Section: Discussionmentioning
confidence: 99%
“…The patients who intentionally ingested FB form a special group. The study reported that the most commonly intentionally ingested objects included razor blades, batteries, and other sharp metallic items, which were not usually reported in the general population, and there was a greater demand for endoscopic and surgical interventions [6].…”
Section: Introductionmentioning
confidence: 99%
“…The need for prompt and effective management of DSH in the healthcare setting stems from the pattern of escalation and the high-risk of mortality among hospitalized patients [12,37]. Of concern, suicide and DSH are among the leading causes of death in the United States, and their incidence is projected to increase over the next 2 decades [38].…”
Section: Discussionmentioning
confidence: 99%